FORMATION OF SUSTAINABLE, EFFECTIVE MODEL OF ECONOMIC SECURITY AT BUILDING ENTERPRISES (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The theoretical aspect of the prognostic formation of a stable, effective model of economic security at construction enterprises is highlighted in the article to improve and develop the system of monitoring economic security at construction enterprises in the new economy. The possibility of approbation of methodological approaches of the formed model at implementation of monitoring of economic safety of construction enterprises is analyzed and characterized. The article defines the conditions for effective functioning and sustainable development of the economic security system at construction enterprises in conditions of unstable economy, taking into account the specific activity in Ukraine. The concepts of the economic security model of a construction company proposed in the article will allow to reach a new level of monitoring of the economic security of a construction company, and will facilitate effective decision-making.The article is intended to deepen and improve the theoretical and methodological foundations of forming a stable and effective model for monitoring the economic security of construction enterprises. To achieve these goals, it is necessary to carry out thorough research of the system of monitoring economic security, to determine the totality of components, their functioning and to ensure the totality of all components in the formation of a model of safety at a construction company.For the effective functioning of a construction company, it is necessary to create structural units that will provide economic security, these structural units are mandatory for medium and large enterprises, and the expediency of their functioning is conditioned at the stage of creation of a construction organization.Formation of an effective model for monitoring the economic security of a construction enterprise is based on considering the economic security of the enterprise in the context of the regional economy, as a set of all its properties, for the progressive development in the conditions of destabilizing influence of various types of internal and external threats.Further studies should be conducted to improve the abovementioned model of monitoring economic security at a construction enterprise, and to adapt this model to domestic construction enterprises and European norms.
Keywords: economic security, monitoring, monitoring approaches, effective model of economy, construction enterprises, innovative management